2018
DOI: 10.1016/j.sjbs.2016.01.037
|View full text |Cite
|
Sign up to set email alerts
|

Phenolic acid content, antioxidant and cytotoxic activities of four Kalanchoë species

Abstract: Phenolic acid composition, antioxidant, and cytotoxic activities in leaves of four (Crassulaceae) species were evaluated. Determination of phenolic acid contents were conducted by an optimized LC-ESI-MS/MS method. The results show that Raym.-Hamet & H. Perrier (using ASE extraction) and (Lam.) Pers. contain the highest amounts of phenolic acids, while Engl. the lowest ones. Among phenolic acids ferulic, caffeic and protocatechuic acids were occurring in the highest quantities in the analysed species. The great… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
71
1
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(80 citation statements)
references
References 18 publications
3
71
1
5
Order By: Relevance
“…Kalanchoe daigremontiana has anti-inflammatory, antimicrobial, antioxidant, and cytotoxic activities [9][10][11][12]. However, the effect of extracts of this plant on cancer cells was tested only on human lymphoblastic leukemia T cells (H9 and J45 cell lines) with estimation of inhibitory concentration values [11].…”
Section: Identification Of Flavonoids and Bufadienolides And Cytotoximentioning
confidence: 99%
See 1 more Smart Citation
“…Kalanchoe daigremontiana has anti-inflammatory, antimicrobial, antioxidant, and cytotoxic activities [9][10][11][12]. However, the effect of extracts of this plant on cancer cells was tested only on human lymphoblastic leukemia T cells (H9 and J45 cell lines) with estimation of inhibitory concentration values [11].…”
Section: Identification Of Flavonoids and Bufadienolides And Cytotoximentioning
confidence: 99%
“…The different activities of K. daigremontiana depend on its phytochemical composition, and its analysis has shown that flavonoids, phenolic acids, and bufadienolides are the main metabolites [8,11,[13][14][15]. To date, only 4 flavonoid compounds of K. daigremontiana have been reported in the literature [8,16].…”
Section: Identification Of Flavonoids and Bufadienolides And Cytotoximentioning
confidence: 99%
“…In plants, most of the antioxidant potential is due to the redox properties of phenolic compounds, which act as hydrogen donors, singlet oxygen quenchers and reducing agents (Kasote et al, 2015). Through various mechanisms, antioxidant activity of polyphenols may act as reducing, chelating and scavenging agent; act as cofactors of enzymes catalyzing oxidative reactions, terminate radical chain reactions, inhibit oxidases, and stabilize free radicals (Bogucka-Kocka et al, 2016). Maillard reaction is responsible for the generation of compounds called melanoidins, brown pigments in roasted coffee, from reducing amino acids and proteins or sugars during food processing and preservation (Wang et al, 2011;Karamac et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…org/10.17306/J. AFS.2018.0587 anticancer and anti-microbial activities and can act as modulators of the activities of enzymes such as XO (Bogucka-Kocka et al, 2016;Danihelová et al, 2012). Moreover, mulberry leaves consist of rutin, isoquercetin, astragalin, which have been shown to be effective antioxidants and XO inhibitors (Chiang et al, 1994;Masuoka et al, 2012).…”
Section: Introductionmentioning
confidence: 99%